Temperature rise in cavities prepared by high and low torque handpieces and Er : YAG laser - Firoozmand, L. [UNESP]; Faria, R. [UNESP]; Araujo, M. A. [UNESP]; di Nicolo, R. [UNESP]; Huthala, M. F. [UNESP] (Nature Publishing Group, 2008)
Objective The aim of this study was to compare intrapulpal temperature increases produced by a high-speed high-torque (speed-increasing) handpiece, a high-speed low-torque handpiece (air-turbine) and an Er: YAG (Erbium: Yttrium-Aluminum-Garnet) laser. Subject and methods Thirty bovine incisors were reduced to a dentine thickness of 2.0 mm. Class V preparations were prepared to a depth of 1.5 mm, measured with a caliper or by a mark on the burs. A thermocouple was placed inside the pulp chamber to determine temperature increases (C). Analysis was performed on the following groups (n = 10) treated with: G1, low-torque handpiece; G2, high-torque handpiece; and G3, Er: YAG laser (2.94 mu m at 250 mJ/4 Hz), all with water cooling. The temperature increases were recorded with a computer linked to the thermocouples. Results The data were submitted to ANOVA and Tukey statistical test. The average temperature rises were: 1.92 +/- 0.80 degrees C for G1, 1.34 +/- 0.86 degrees C for G2, and 0.75 +/- 0.39 degrees C for G3. There were significant statistical differences among the groups (p = 0.095). All the groups tested did not have a change of temperature that exceeds the threshold of 5.5 degrees C. Conclusion Temperature response to the low and high torque handpieces seemed to be similar, however the Er: YAG laser generated a lower temperature rise.